MODELING OF SUPPLY AND DEMAND FOR MAIZE IN KILIFI DISTRICT, KENYA: A COBWEB MODEL APPROACH - Ronald, Koech; Willy-Marcel, Ndayitwayeko; Charles, Karani (IJRDO - Journal of Business Management, 2018)
The study aimed at assessing the determinants of demand and supply of maize in Kilifi, Kenyausing the cobweb model for analysis. Results showedthat variations in production of maize wereexplained by the prices of cassava, income per capita of consumers and time trend. Price ofcassava (maize substitute) werestrongly significant (p<0.01) and had expected negative sign.This implied that if the price of cassava increased, farmers would shift from maize production tocassava production. In the model, an increase of price of a bag of cassava by 1 US$ woulddecrease the production of maize by 0.95 per cent in the long-run. Income per capita ofconsumers was significant (p<0.1) though with unexpected sign. The study established that thereis need for intensification of maize production due to its importance through provision of theprerequisite incentives such as extension and inputs.